TThe Effect Of Compensation And Job Satisfaction On Employee Performance Employees At Optimate Holistic Company Kebo Iwa Branch - Ade Baghdad Cavalera (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The success of the company in achieving its success is determined by human resources who are involved in the process of the company's activities. The high or low performance provided by employees can be influenced by the job satisfaction experienced by employees and the compensation provided by the company to employees. This study aims to analyze the effect of compensation and job satisfaction on employee performance at Optimate Holistic Kebo Iwa Branch. The study was conducted on Optimate Holistic employees of Kebo Iwa Branch, with a sample size of 46 individuals, using the probability sampling method. The data analysis approach used is Multiple Linear Regression Analysis. The findings of this study indicate that all hypotheses are acceptable. The compensation factor has a positive and significant impact on employee performance, while job satisfaction also has a positive and significant influence on employee performance. Together, compensation and job satisfaction have a positive and significant impact on employee performance. Good compensation can trigger a good relationship where employees feel safe and comfortable at work. The fulfillment of employee rights supported by employee job satisfaction can have a positive impact on improving employee performance. This research is able to make a practical contribution as a consideration for the leaders of Optimate Holistic Kebo Iwa Branch in improving the performance of its employees.